Mitogenome and Nuclear-encoded Fungicide-target Genes of Thecaphora frezii - Causal Agent of Peanut Smut - Arias, Renee S.; Cazon, Luis Ignacio; Massa, Alicia N.; Scheffler, Brian E.; Sobolev, Victor S.; Lamb, Marshall C.; Duke, Mary V.; Simpson, Sheron A.; Conforto, Erica Cinthia; Paredes, Juan Andrés; Soave, Juan H.; Buteler, Mario I.; et al. (Longdom Publishing, 2021)
Background: Thecaphora frezii Carranza and Lindquist causes smut disease in peanut (Arachis hypogaea L.) resulting in up to 35% yield losses. Fungicides have shown ineffective in controlling the disease; whereas research on the molecular basis of that fungicide resistance has been hindered because of the lack of genetic information about T. frezii. The goal of this work was to provide molecular information about fungicide-target loci in T. frezii, including its mitochondrial genome (mitogenome) and critical nuclear-encoded genes. Results: Here we report the complete annotated mitogenome of T. frezii, a 123,773 bp molecule containing the standard 14 genes that form part of mitochondrial complexes I, III, IV and V, 22 transfer RNAs, small and large subunits of ribosomal RNA, DNA polymerase, ribonuclease P, GII-reverse transcriptase/maturase, nine hypothetical open-reading frames and homing endonucleases (LAGLIDADG, GIY-YIG, HEG). In addition, we report the full-length cDNA sequence of T. frezii cytochrome b (cob) and cytochrome oxidase 1 (cox1) genes; as well as partial sequences of T. frezii succinate dehydrogenase (sdhb), ergosterol biosynthesis (Erg4), cytochrome P450 (cyp51), and beta tubulin (β-tubulin) genes, which are respective targets of strobilurins, quinone oxidation inhibitors, triazoles and beta-tubulin inhibitor fungicides commonly used in the peanut crop. Translation of cob and sdhb genes in this particular T. frezii isolate suggests potential resistance to strobilurin and carboxamide fungicides. Conclusion: The mitogenome and nuclear-encoded gene sequences presented here provide the molecular tools to research T. frezii fungicide-target loci.